Strengthening Leadership Values and Positive Behavior Through the Character Building Leadership Program for OSIS Members of SMK Al-Amanah - Djihadah, Nurhayati; Latief, Abdul; Ningrum, Listya; Ayu Dita, Diana; Hastuti, Sri; Mulyawan, Yandi; W, Wahyudi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The Intra-School Student Organization (OSIS) serves as a leadership laboratory for students and requires strong, competent human resources to act as agents of change within the school. This program aims to strengthen leadership values and shape positive behavior among OSIS members at SMK Al-Amanah through a Character Building Leadership approach combined with experiential learning methods. The activity was carried out on October 30, 2025, involving 42 OSIS members (core administrators and active members) through a series of interactive workshops, discussions, and educational games (outbound leadership games). The implementation method focused on three main simulations: Chain Sentences to train effective communication, Nail-in-the-Bottle to build team coordination, and Rubber Band Relay to develop focus and trust. Evaluation was conducted through behavioral observation during the games, value reflection, and pre-test and post-test trigger questions. The results of the activity indicate that experiential learning methods effectively enhanced participants’ understanding of responsibility, integrity, and teamwork. Qualitatively, participants showed significant improvement in group solidarity and organizational communication skills. It is concluded that the program successfully instilled positive leadership foundations and is recommended to be continued through weekly leadership coaching.